Erythrina—chemical and pharmacological evaluation II: Alkaloids of erythrina variegata L - Ghosal S.; Dutta S.K.; Bhattacharya S.K. (My University, 2025)
Eight spiroamine alkaloids (I‐VIII) and three carboxylated indole‐3‐alkylamines (IX‐XI) were isolated from the various parts of Erythrina variegata, and their identity was established by chemical and spectral (UV, IR, NMR, and mass) methods. Of the eight spiroamine bases isolated, three (I, VI, and VII) were previously unreported in nature, while methyl esters of hypaphorine (X) and N,N‐dimethyltryptophan (XI) were isolated for the first time from this genus. Isolation of the two alkaloids (VI and VII), which lie in the natural biosynthetic pathway to the aromatic erythrina alkaloids, is of considerable biogenetic and chemotaxonomic significance. Selected pharmacological studies with the total alkaloid fraction from the bark showed several characteristic pharmacological effects: neuromuscular blocking, smooth muscle relaxant, CNS depressant, hydrocholeretic, and anticonvulsant effects, which are consistent with the reported uses of the plant extracts in the indigenous system of medicine. Copyright © 1972 Wiley‐Liss, Inc., A Wiley Company